SiniLoyal: Enhancing Marketing and Public Services Through Siniloan Market’s Loyalty Card - Urera, Flaviano Llames; Jain, Archieval M. (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose – The purpose of this study is to design and evaluate SiniLoyal, a digital loyalty card in enhancing marketing and local services within the public markets. Additionally, it applies predictive analytics and the assessment using Technology Acceptance Model (TAM) on the criteria of perceived usability. Method – D escriptive and developmental method based on the Rapid Application Development (RAD) model, wherein information from LGU officials, Sangguniang Bayan, vendor associations, and related studies were integrated. Using TAM framework, 273 consumers and 241 vendors assessed the system. ARIMA and SARIMA forecasting enabled the predictive analysis of seasonal spend behaviors to improved market strategy. Results – SiniLoyal earned high acceptability, consumers rating 4.23 and vendors 4.30. Grand mean 4.02 and 4.12 acceptable respectively. There are significant differences in perceived usefulness and ease of use, p-value less than 0.05, which indicates the need for engagement level. The forecasting module achieved over 85% accuracy, correctly predicting periodic demand. QR-based purchases gave tiered rewards instant points updates, while collected data highlighted trends that help sales optimization and marketing strategies. Conclusion – Loyalty mechanisms driven by predictive analytics with QR based transaction and LGU participation would promote a more transparent, efficient, and engaging public market operation. Recommendations – Improved system features, transactions and incentives would attract more users. Collaborate with key partners LGU-SB and DTI reinforce awareness and adoptability; limited sample size requires testing in other markets. Future improvements should focus on better rewards, working more with market group, improving mobile accessibility for broader adoption. Research Implications – Sustainable utilization to public market of SiniLoyal application convert traditional market into digital loyalty consumer-vendors engagement while integrating local service governance. Its expansion can strengthen local economies, provide respondent-driven insights, and serve as national model for enhancing and refining public market operations.